The Role of Women in The Implementation of Religious Moderation in The Family Environment in the 4.0 Era - Zahro, Indah Rohmatuz; Musya’adah, Umi (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Women who become mothers in the family have a very crucial role in classifying the values of religious moderation in the family environment, especially in the 4.0 era. As Madrasah Al-ula in children's education. Women who become mothers are role models for their children, therefore mothers become role models, so mothers should carry out their children's education duties well, so that in the future it is hoped that a good generation will also be formed. As the main educator for children in the 4.0 era, there are many challenges faced where the flow of information that is fast and easily accessible can spread radicalism. This paper aims to analyze how the role of women in educating children to grow up to be moderate and moral individuals in the midst of digital information flow.